The Function Of Spatial Planning In Maintaining The Environmental Preservation Of West Pasaman District - Rahmadani Siregar, Dewi; Azzahra, Nabila; Fajri, Muhammad; Amini, Aisyah; Hari Asri, Hazqan; Setiawan, Arif; Oktavia, Elfitri; Suhendrinal; Haryeni; Jelibseda; Nurhasan Syah; Heldi; Catri, Indra; Dewata, Indang; Barlian, Eri; Umar, Iswandi; Kamal, Eni (Jurnal Ilmiah Platax, 2025)
Abstract: This research examines the role of spatial planning in preserving the environment in West Pasaman Regency. The main aim of this research is to evaluate how the implementation of spatial planning can support environmental conservation efforts. The method used is qualitative descriptive analysis with a case study approach. Data was collected through in-depth interviews, field observations, and analysis of spatial planning documents. The research results show that good and well-planned spatial planning can reduce pressure on natural resources and improve the quality of the living environment. However, challenges such as weak law enforcement and low public awareness are still the main obstacles. In conclusion, the integration of spatial planning policies that pay attention to environmental aspects is very crucial to achieving sustainable development in West Pasaman Regency. Keywords: Environment; Spatial; Continuity;   Abstrak Penelitian ini menelaah peran tata ruang dalam menjaga kelestarian lingkungan hidup di Kabupaten Pasaman Barat. Tujuan utama dari penelitian ini adalah untuk mengevaluasi bagaimana implementasi tata ruang dapat mendukung upaya pelestarian lingkungan. Metode yang digunakan adalah analisis deskriptif kualitatif dengan pendekatan studi kasus. Data dikumpulkan melalui wawancara mendalam, observasi lapangan, dan analisis dokumen perencanaan tata ruang. Hasil penelitian menunjukkan bahwa tata ruang yang baik dan terencana dapat mengurangi tekanan terhadap sumber daya alam dan meningkatkan kualitas lingkungan hidup. Namun, tantangan seperti lemahnya penegakan hukum dan rendahnya kesadaran masyarakat masih menjadi hambatan utama. Kesimpulannya, integrasi kebijakan tata ruang yang memperhatikan aspek lingkungan sangat krusial untuk mencapai pembangunan berkelanjutan di Kabupaten Pasaman Barat. Kata Kunci : Lingkungan; Tata Ruang; Keberlanjutan;